STRATEGI PEMIMPIN DALAM MENINGKATKAN KUALITAS KINERJA KARYAWAN DI BMT MUAMALAH TULUNGAGUNG - Sultoni, Hasan (LIPI, 2019)
This research aims to know the leader strategy in improving the quality of employees ' performance at BMT Muamalah Tulungagung. The research method used is qualitative research. This type of research uses descriptive analysis, in the process of research the data collected in the form of words and observations to a company in the direction.The results of this study showed that BMT Muamalah Tulungagung leadership strategy was good enough. The strategy leader in the management of BMT MUAMALAH Tulungagung, namely: motive, benefits, good communication, supervision, and evaluation. While in the research results the role of leaders to improve the performance quality of employees BMT Muamalah Tulungagung, namely: Clear job description, Solidarity team work, compliance with work procedures, freedom of employees to work, responsibility Responsibilities, hospitality in the works, changes in the work, the attitude of mutual openness.